Aulton's pharmaceutics : the design and manufacture of medicines - Aulton, Michael E.; Taylor, Kevin, 1961- (Elsevier, 2018)
A comprehensive textbook covering the design of dosage forms and all aspects of drug delivery systems. Pharmaceutics in its broadest sense is the 'art of the apothecary' or, in simple terms, pharmaceutical preparations. It remains a diverse subject in the pharmacy curriculum, encompassing design of drugs, their manufacture and the elimination of micro-organisms from the products. This books encompasses all of those areas.